Effect of the sodium and potassium nitrate on the quality uf pastrami during storage period - Yusuf Doğruer; Suzan Yalçın; Ümit Gürbüz; Ahmet Güner (Eurasian Journal of Veterinary Sciences)
Different levels ol sodium and potassium nil rates (control. 1 %, 2% and 3%) were applied to pastrami during the salting process. And possible effects of this practice on the chemical and microbiological quality of pastrami were investigated at the 1st, 7th. 15th, 30th and 60th days of the storage penod The salt levels, pH and aw values of pastrami samples were found between 4.26-5.21%, 5.57-6,16 and 0.882-0.914 at the 1st day between 7.18-8.43%. 5.84-6.25 and 0.742-0.779 at the 60th day respectively, Remerkable differences have been found between groups in the amount of hu-midty according to nitrate rations at the 30th day. According to the microbiological results, the number of total mesophlic aerobic. Staphylococcus-Micrococcus, Lactobacillus microorganisms, mould and yeast of pastrami samples did not change sıgnıtıcantly during the storage period. On the other hand coliform group microorganisms were not cultivated in all phases. In conclusion, it was determined lhat treatments with different nitrate salts and levels had not an effect on the chemical and microbiological properties of pastrami samples.